Comparing Postoperative Analgesic Effect of Subcostal Transverse Abdominis Plane Block and Intraperitoneal Installation of Ropivacaine after Laparoscopic Cholecystectomy - Archih Singh; Gaurav Misra; Juhi Saran (Academia Anesthesiologica International, 2024)
Background: Laparoscopic cholecystectomy(LC) is a prevalent surgical procedure. A substantial portion of surgical pain originates from incisions of the abdominal wall, receiving sensory input from T6-L1 afferent nerves traversing the neurofascial plane between the internal oblique and transversus abdominis muscle. The subcostal transverse abdominis plane (TAP) block is effective for alleviating postoperative pain in upper abdominal surgeries. Hence, we aimed to assess postoperative analgesic effects of subcostal TAP block and intraperitoneal installation of ropivacaine after LC. Subjects and Methods: In this prospective comparative study, 54 patients were equally and randomly assigned to each group. Group I participants received 40ml of Intraperitoneal ropivacaine 0.25% instilled on the liver bed, while Group T participants underwent an ultrasound-guided subcostal TAP block with 40ml of ropivacaine 0.25%. Demographic and hemodynamic parameters were documented, and pain levels were evaluated using the Numerical Rating Scale (NRS) and Visual Analog Scores (VAS). Data regarding the need for rescue analgesia and the incidence of postoperative nausea and vomiting (PONV) were also recorded. Results: In the present study, no significant difference was noted in the demographical parameters. Haemodynamics were comparable among both groups. VAS scores were significantly lower in group T than I. In Group T, a significantly lower number of patients (n=9) needed rescue analgesia in comparison to Group I (n=23) (p=0.0001*). PONV was reported in 9 patients in Group I, whereas only 3 patients from Group T exhibited these symptoms (p=0.0495*). Conclusion: The ultrasound-guided subcostal TAP block is a highly effective adjunctive method in multimodal post-operative analgesic approach.